Laporan Baru: Spesies Lalat Buah Terpikat 4-(4-Hidroksi-Fenil)-2-Butanon - Deni Pranowo; Edhi Martono; Ahmad Taufiq Arminuddin; Suputa Suputa (Universitas Gadjah Mada, 2009)
Acetylation of 4-(4-hydroxy-penyl)-3-butene-2-one by anhydride of acetic acid catalyzed by sulphuric acid results in 4-(4-acetoxy-phenyl)-3-butene-2-one compound, and 4-(4-hydroxy-phenyl)-2-butanone compound as a by product. The first compound alone doesn’t attract fruit flies, but a mixture of the two products attracts male fruit flies. This mixture was tested for its attractancy to the fruit flies in Bantul, Sleman and Kulon Progo regencies, Yogyakarta Special Province; along with Cue and Methyl eugenol lures as comparison. The result showed that the mixture was able to attract four fruit flies species, i.e. Bactrocera albistrigata, B. caudata, B. cibodase, and Bactrocera sp1. One genus found has not been able to be identified to species level. Based on its wing morphometric measures, this species is put under Bactrocera dorsalis complex group.